Implikasi Study Kearney Terhadap Proses Marger Industri Perbankkan Indonesia - Budi Manggala (Jurnal Ekonomi, 2001)
Banking recapitalization policies have been going on for more than two years. On the one hand, there are signs of improvement. However, on the other hand, there are matters that have to be observed and to find a solution for. Transfer of portfolio pf bad debt from the national banking to the Indonesia Bank Restructuring Agency (IBRA) and exchanged it with additional capital in the form of government bonds have caused the earning capacity to be dependent on the payment of bonds interest. However, those banks which have received additional capital through the recapitalization program are now threatened by the decrease of their capital adequacy ratio (CAR) and are still not able to deliver significant contributions to support the real sector. The objective of this article is to describe Kearney’s survey about the implementation of mergers in the international banking industry. Based on Kearney’s observation will cause a significant stimulus for Indonesia's banking industry at the current time.